ANALYSIS OF LEGAL PROTECTION REGARDING THE COMPANY'S LARGE PROJECT ON FOREIGN DIRECT INVESTMENT IN INDONESIA - Muhammad Akbar Hanif Pradana; Mutiani Fadly; Shania Monalisa Batubara; Adelista Firda Destyaningsih (Problematika Hukum, 2023)
Foreign investment is necessary to support the growth anddevelopment of the national economy in Indonesia. One of the mainresources to support national development is foreign capital payments.There are many factors that foreign investors must consider beforeinvesting in Indonesia. The first is the legal protection imposed by thegovernment on foreign investors. According to Law Number 25 of2007 concerning InvestmentThis research aims to analyze the relationship between foreigninvestment in Indonesia. This research uses a normative approach,meaning the aim is to measure or evaluate something based on existingstandards or norms, in this case, legal norms. The statutory regulatoryapproach method is different from the approach that uses law as themain tool to analyze a particular issue or problem.This transfer of knowledge and technology also benefits a lotfromforeign investors, namely increasing state income or foreign exchangein the investor's home country (Harjono, 2016). Legal protection isone component that supports the growth of foreign investmentbusinesses in Indonesia.Keywords:Foreigninvestment;Investment Law;LegalProtection;